Activities of the International Research Centre for Late Antiquity and Middle Ages in 2007 - Jurković, Miljenko; Turković, Tin (2008)
An Editorial describing the activities of IRC for Late Antiquity and Middle Ages (Zagreb-Motovun) in 2007: implementation of the IRCLAMA project, financed through the 6th Framework Programme of the European Commission ; publishing of the first volume Velika Gospa pres de Bale (Istrie) I. L'eglise Velika Gospa pres de Bale Vol I (ed. Miljenko Jurković, Jean-Pierre Caillet), Zagreb-Motovun, 2007 ; the field researches on the Island of Rab, in Guran (Istria) and Osor (Island of Cres), "Corpus of European architecture of the first millennium" etc.
Projekt MZOS
ENG